PERAN DINAS PARIWISATA KABUPATEN LAMPUNG TIMUR DALAM PENGELOLAAN TAMAN NASIONAL WAY KAMBAS - Tia Marlinda Sari; Lucky Salilana (JURNAL DINAMIKA, 2021)
One of attraction icon in Lampung Province is Way Kambas National Park, East Lampung. The issue of road infrastructure as well as the general facilities less attention to the goverrnment’s attention, especially the East Lampung Regency Tourism Office while such public facilities are one of the convenience factors of local travelers and foreigners. This study uses a qualitative analysis method in a descriptive way, namely by conducting interviews, observation and documentation by focusing on the role and barriers of the East Lampung Tourism Office in the management of Way Kambas National Park. The result showed has been a significant increase in the number of visitors coming to Way Kambas National Park thanks to the promotion activities that were intensively carried out by the East Lampung Tourism Office. The distance that must be taken to get to the tourist area. Lack of awareness of the surrounding community to protect the environment around tourist attractions so that there is still a large amount of scattered waste which is one of the obstacles in the management of Way Kambas National Park that has not been resolved.